Encouraging voluntary work among public service retirees: how policy intervention can help - Uttam Singh, Surjit Singh; Md. Sail, Rahim; Abu Samah, Bahaman; Lumayag, Linda Alfarero (Universiti Putra Malaysia Press, 2005)
This paper is part empirical and part theoretical. It argues that for volunteerism to be a permanent feature in the society there must be a public policy that encourages, motivates and appreciates the value of volunteerism, and that it should be consciously acknowledged in the community. To be able to create this sense, a new developmental view on the contributive roles of the ageing population must be in place in the policy intervention. Malaysia, a rapidly industrializing country in the Asian region, must recognize the fact that a great number of willing and committed retirees could be tapped as potential volunteer workers for the continuing development of the broader community.